Just Execution with Permanent Legal Force - Anak Agung Ngurah Alit Wiraputra; Yohanes I Wayan Suryadi (Warmadewa Press, 2025)
The execution of a civil case decision that has permanent legal force often experiences obstacles in its implementation, and is even difficult to implement. This is contrary to the principles of a simple, fast, and cost-efficient justice system, especially in the execution process. The applicant for execution, who hopes that his rights can be fulfilled by the respondent, is often burdened by high execution costs, even though the execution is carried out not due to the applicant's fault, but due to the respondent's unwillingness to voluntarily implement the decision. In this case, the aim is to analyze the regulation of the execution of civil case decisions that do not reflect justice, identify weaknesses in the implementation of the execution of civil cases that have permanent legal force, and provide a concept of justice-based execution reconstruction. The approach used in this study is normative juridical with a post-positivism paradigm, as well as through the approach of laws, concepts, comparisons, and cases. It can show that the current execution regulation does not provide a sense of justice, with the existence of legal uncertainty and problems in the execution procedure. Weaknesses in the legal substance in the HIR/RBg, as well as structural weaknesses and legal culture, are the main factors in the ineffectiveness of the execution of civil case decisions. Legal reconstruction includes changes to related articles in the HIR and the General Courts Law, as well as the establishment of a special institution that handles confiscation and execution. So that a fairer execution concept can be created and provide legal certainty for execution applicants.